Resistance training considerations for female surfers - Anthony, C. C.; Brown, L. E. (Strength and Conditioning Journal, 2016)
Gender is a major contributor to performance differences in surfing. Male and female surfers have different needs regarding physical fitness and athletic performance. Developing a female-specific training program that addresses physiological limitations while also mimicking the sport-specific demands of surfing may assist in reducing the performance gap between genders. Therefore, the aim of this article is to elucidate the physiological demands of surfing, the needs of female surfers, and suggest a progressive sport-specific training program involving phases of hypertrophy, strength, and power.